Epidemiological Analysis of the Incidence of Hemorrhagic Fever with Renal Syndrome in the Jewish Autonomous Region in 2003 - 2016 - E. I. Andaev; A. V. Sevostianova; N. V. Breneva; A. K. Noskov; P. V. Kopylov; Y. G. Beznogov; I. P. Snetkova; L. N. Avdoshina; S. V. Balakhonov (Эпидемиология и вакцинопрофилактика)
Retrospective epidemiological analysis of hemorrhagic fever with renal syndrome (HFRS) was performed in the Jewish Autonomous Region based on archival, statistical and operational data of 133 HFRS cases. Total 63 mammal samples were examined by ELISA and RT-PCR. Large-scale flooding in 2013 sharpened the epizootological condition and created the preconditions for epidemiological complications. The high increase in HFRS incidence in 2014 was characterized by the epidemiological process intensity displacement from the southern areas to least affected by flooding northern parts of the region and alteration of the seasonality corresponding to the maximum number of carriers in natural foci. Since 2015 a decrease of morbidity is observing. RNA and antigen of Hantaviruses were found in Apodemus agrarius and Microtus maximowiczii. Sequencing of L-gene fragment (334 bp) of RNA-containing samples showed their taxonomic affiliation to the three Hantaviruses: Khabarovsk, Hantaan and Puumala.